KIT-6 supported PhAA-Pd complex as a sustainable nanocatalyst for C–O coupling reactions - Abdulrahman A. Almehizia; Munthar Kadhim Abosaoda; Anjan Kumar; Vicky Jain; Suhas Ballal; Abhayveer Singh; Mamata Chahar; Suman Saini; Kamal Kant Joshi; Abhinav Kumar (Scientific Reports)
Abstract A practical and efficient method for synthesizing C–O cross-coupling has been established using a Pd complex anchored on mesoporous KIT-6. This design showcases exceptional efficiency, recoverability, and thermal stability. The synthesized mesostructure underwent comprehensive characterization through techniques such as FT-IR, SEM, XRD, EDX, BET, ICP, and TGA analyses. This catalyst was then successfully applied in C–O cross-coupling reactions. The approach offers several advantages, including rapid reaction times, high yields, excellent product purity, simplicity, environmental friendliness, and straightforward work-up procedures. Importantly, the durable nanohybrid catalyst exhibited no metal leaching and retained its catalytic performance across multiple cycles of use.